Si Carancal laban sa ilalim ng dagat Carancal under the sea - Villanueva, Rene O. (Adventures of Carancal, 2007)
In this story, wherein Carancal goes to the sea to comfort a ferocious creature, the author gives emphasis to the concern for endangered animals and environment as well as love for others.